CONCEPT OF SHUSHKAKSHIPAKA (DRY EYE SYNDROME) IN AYURVEDA WITH MODERN COUNTERPART: A REVIEW (AYUSHDHARA, 2020)
Eyes are the windows to the soul. Ayurvedic classical texts have mentioned about eye and its diseases since Vedic and Samhita kala, thus showing the importance of eye and ways to protect it. That is why eye care has been one of the priorities since the ages. In Ayurveda clinical features related to Dry eye are generally seen in Suskaksipaka.Over use of Video Display Terminals (V.D.T) like Computer, Mobiles, and Television & faulty lifestyle are some of the causes. Among these disorders, many are related to Indriya (Sensory Organ) especially Caksurindriya (Eye). In metro city, more than 50% cases from ophthalmic OPD are of Dry Eye Syndrome. Dry Eye Syndrome is a common ophthalmic condition, in its real sense is a problem for eye care practitioners due to its variegated etiologies, multi factorial physiopathology, lack of gold standard for diagnostic procedure. No curative treatment modalities are available and the palliative measures are inadequate too. It presents a great challenge to physicians. That’s why its prevalence is very high. It is 5% to 35% worldwide, while in India it is 29.25%. Dry Eye Syndrome also known as Kerato-Conjunctivitis Sicca (KCS) is considered a disease of the modern era. Dry eye syndrome, one of the most frequently encountered ocular morbidities, a growing public health problem and one of the most common conditions seen by the eye care practitioners. Tear secretion provides continuous moisture and lubrication on the ocular surface and provides oxygen to the corneal- epithelium. When the normal tear production is compromised, it leads to dry eyes.